The role of the vesicular monoamine transporter 2 in the inhibitory effect of tetrabenazine and valbenazine compared to reserpine on the vesicular release of monoamine transmitters - Maácz, Fruzsina; Bán, Erika Gyöngyi; Brassai, Attila; Sperlágh, Beáta; Vizi, E. Sylvester (Frontiers in Cellular Neuroscience, 2025)
BackgroundVesicular monoamine transporter 2 (VMAT-2) plays a vital role in packaging cytosolic monoamine transmitters into axon terminal vesicles, which can be released in response to action potentials. Reserpine (RSP), a classical irreversible inhibitor of the monoamine transporter, is an alkaloid used as an antihypertensive drug. However, its use in medicine was very short-lived because of side effects (depression, Parkinsonism). Tetrabenazine (TBZ) and valbenazine (VBZ), biochemically non-competitive and reversible VMAT-2 inhibitors, are both used in the treatment of Tardive Dyskinesia (TD). The aim of this study was to directly compare the effects of RSP, TBZ, and VBZ on vesicular storage and exocytotic release of monoamines in hippocampal slices, and to clarify whether their actions differ in terms of reversibility and persistence. Our work addresses the biological question of how these clinically relevant VMAT-2 inhibitors modulate monoaminergic neurotransmission at the synaptic level.Materials and methodsVesicular storage capacity and release of [3H] noradrenaline ([3H] NA), [3H] serotonin ([3H] 5-HT), and [3H] acetylcholine ([3H] ACh) were studied in mouse hippocampus ex vivo slice preparations using electrical field stimulation.ResultsIn this study, for the first time, direct neurochemical evidence was obtained that RSP reduces the vesicular storage capacity and the exocytotic release of [3H] NA and [3H] 5-HT evoked by axonal stimulation from the ex vivo hippocampal slice preparations and failed to influence the plasma membrane uptake of monoamines and exocytotic release of [3H] ACh. The inhibitory effect of RSP on vesicular release, neurochemically proven to be irreversible, was not accompanied by a recovery in VMAT-2 enzyme activity, as observed in biochemical studies. TBZ and VBZ are compared to RSP in that they also inhibit the vesicular release of neurotransmitters and storage capacity; however, their activity is less effective and is of much shorter duration, leaving some time for vesicle refilling.DiscussionThe difference observed between the two types of VMAT-2 inhibitors might give some explanation of why, in response to TBZ or VBZ treatment, the occurrence of depression or Parkinsonism as side effects is seen very rarely or not at all, and in the case of RSP, it is relatively frequent.